Double-headed sulfur-linked amino acids as first inhibitors for betaine-homocysteine S-methyltransferase 2 - Mládková, Jana; Vaněk, Václav; Buděšínský, Miloš; Elbert, Tomáš; Demianová, Zuzana; Garrow, Timothy A; Jiráček, Jiří (Journal of medicinal chemistry, 2012)
Betaine-homocysteine S-methyltransferase 2 (BHMT-2) catalyzes the transfer of a methyl group from S-methylmethionine to l-homocysteine, yielding two molecules of l-methionine. It is one of three homocysteine methyltransferases in mammals, but its overall contribution to homocysteine remethylation and sulfur amino acid homeostasis is not known. Moreover, recombinant BHMT-2 is highly unstable, which has slowed research on its structural and catalytic properties. In this study, we have prepared the first series of BHMT-2 inhibitors to be described, and we have tested them with human recombinant BHMT-2 that has been stabilized by copurification with human recombinant BHMT. Among the compounds synthesized, (2S,8RS,11RS)-5-thia-2,11-diamino-8-methyldodecanedioic acid (11) was the most potent (K(i)(app) ∼77 nM) and selective inhibitor of BHMT-2. Compound 11 only weakly inhibited human BHMT (IC(50) about 77 μM). This compound (11) may be useful in future in vivo studies to probe the physiological significance of BHMT-2 in sulfur amino acid metabolism.
Keywords: kinetika; rekombinantní proteiny; homocystein; enzymatické testy; Betaine-Homocysteine S-Methyltransferase; stereoizomerie; sulfidy; betain-homocystein-S-methyltransferasa; vztahy mezi strukturou a aktivitou; Humans; Sulfides; Enzyme Assays; Homocysteine; Structure-Activity Relationship; Stereoisomerism; lidé; Recombinant Proteins; Kinetics